NEW CONCEPT FOR DIGITAL INCLUSION—ONLINE AND MOBILE LEARNING PROGRAMS FOR OLDER PERSONS - Lipphardt, Anne-Marie; Leen-Thomele, Eline; Coroian, Anamaria Elena; Held, Paul (Innovation in Aging, 2017)
This paper sums up the evaluation results of two e-learning ICT courses for older adults: a tablet computer course and a regular computer course, and discusses the advantages of mobile learning and e-learning for older adults. As part of an European research project, the SenApp project, online course modules were developed, to teach older adults the first steps on a tablet computer, and evaluated (N=37, age range 58–93). The other course we analyzed, was an online learning course with regular computers and part of the LernHaus project in Germany (N=29, age range 50–89). The evaluation focused on differences in satisfaction with support and course contents and in learning routines between age groups, education level, countries and pre-experience conditions. Main findings suggest that all courses were rated good, compliance was very good and that support was a key factor for course success. Mobile learning was slightly easier for new learner

Older Adults and Learning Technology: Innovations in Adults‘ and Seniors‘ Education - Lipphardt, Anne-Marie; Leen-Thomele, Eline; Held, Paul; Coroian, Anamaria Elena (Innovation in Aging, 2017)
This paper discusses the results of an empirical survey with 187 peopleabove the age of 50 years (mean age 68,4 yrs) on their digital behaviors, motivation as well as interests, and barriersagainst the use of new technologies and presents innovative learning approaches for older adults. The interviewswere conducted in five European countries (Finland, France, Germany, Ireland, Spain) as part of the research projectEHLSSA. The findings show that more than half of older adults are computer users and have Internet access at home.Reasons why they deal with digital technologies are mainly because they want to participate in the information societyand keep pace with the younger generation. Main obstacles are physical challenges, fears and reservations totechnology and the Internet, insecurity on how to work with digital devices and with regards to possibilities for supportin case something goes wrong or questions arise. According to the interviewees, successful learning concepts focuson experimental and active learning, including a more diverse media use, a series of real life examples, and theconnection with the daily life of older adults. Responses of ICT-beginners and experienced ICT-users were analyzedseparately and compared. The results have been used as the basis for the adaptation of learning approaches for thirdlevel education and the development of online course modules in the field of digital literacy and humanities-relatedtopics. The implementation of these courses started in May 2016 and will be completed in June 2017 with at least 800 participant